PENGARUH MEDIA KALENDER PINTAR OBAT BEBAS TERHADAP PENGETAHUAN DAN SIKAP DALAM MEWUJUDKAN GEMA CERMAT - badarul, aura; Fadli (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2021)
ABSTRACT Along with changes in the lifestyle of people who tend to pay less attention to health, disease development in the community is inevitable. Providing education about medicine through smart calendars to the public can overcome this problem. Calendar is designed to improve thinking skills and stimulate adolescents' thinking, including concentrating and solving problems against changes in knowledge and action. This study aims to determine whether there is an effect of innovative calendar media for learning over-the-counter drugs on knowledge and attitudes in realizing the intelligent community movement using drugs. Were conducted this research with a quantitative survey method by collecting data via a google form. The sampling method uses probability sampling with a simple random sampling technique. Sampling was conducted on 140 adolescents at SMA Negeri 1 Kendawangan, then obtained a sample of 116 respondents. Data analysis used the Kolmogorov-Smirnov test for normality, Wilcoxon test for hypothesis testing of knowledge and attitudes. The level of confidence used is 95%. The results showed an increase in the number of respondents between the pre-test and post-test. With an Asymp.sig (2-tailed) value on knowledge and attitude of 0.000. So it can be concluded that there is an effect of using free drug calendar media on the inside and attitudes of class XI students of SMA Negeri 1 Kendawangan.